Produksi Asap Rempah Cair dari Limbah Padat Rempah dengan Cara Pirolisa - Purnama Darmadji; Supriyadi Supriyadi; Chusnul Hidayat (agriTECH, 1999)
The new product liquid of moke from solid wastes of spices were produced by pyro 'zation for development the extraction process. The research materials were solid wastes from distillation of spices. Pyrolization process was carried at 150, 200, 250 and 300°C for 30 minutes each process. The products were evaluated for antimycrobial and antioxidation activities as well as sensory qualities. The results indicated that antimycrobial activities of the spices liquid smokes from "Eugeria" leaf and "Zingiber" increased with an increasing of pyrolization temperature while spices liquid smoke from "Citronella" leaf was higher at 150°C and decreased with increasing temperature. The antioxidation activities of spices liquid smokes were varied depended on pyrolization temperatures. The flavor of spices were dominant at 150°C pyrolization, and have a moderate mixed flavor of spices and smoke at 200°C pyrolization